The liver pharmacological and xenobiotic gene response repertoire - Georges Natsoulis; Cecelia I Pearson; Jeremy Gollub; Barrett P Eynon; Joe Ferng; Ramesh Nair; Radha Idury; May D Lee; Mark R Fielden; Richard J Brennan; Alan H Roter; Kurt Jarnagin (Molecular Systems Biology)
Abstract We have used a supervised classification approach to systematically mine a large microarray database derived from livers of compound‐treated rats. Thirty‐four distinct signatures (classifiers) for pharmacological and toxicological end points can be identified. Just 200 genes are sufficient to classify these end points. Signatures were enriched in xenobiotic and immune response genes and contain un‐annotated genes, indicating that not all key genes in the liver xenobiotic responses have been characterized. Many signatures with equal classification capabilities but with no gene in common can be derived for the same phenotypic end point. The analysis of the union of all genes present in these signatures can reveal the underlying biology of that end point as illustrated here using liver fibrosis signatures. Our approach using the whole genome and a diverse set of compounds allows a comprehensive view of most pharmacological and toxicological questions and is applicable to other situations such as disease and development.